First record of Petelia distracta in Uttar Pradesh, India, and the novel observation of puddling behavior in (Geometridae:Ennominae) from India - Taslima Sheikh; Ratindra Pandey; Rupak De; Abu Arshad Khan (Journal of Fauna Biodiversity, 2024)
This study documents the first occurrence of Petelia distracta (Walker, 1860) in Uttar Pradesh, India. Additionally, it reports the unprecedented behavior of these moths engaging in nocturnal puddling on cow dung and wet old leaf. The observations contribute to the understanding of puddling behavior in Geometridae for the first time in India, offering new insights into the ecological interactions and resource utilization strategies of nocturnal Lepidoptera.